Was hält die Gesellschaft noch zusammen? Politische Bildung in einer entgrenzten Zeit - Klaus Peter Hufer (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2017)
The following article describes the situation of political adult education in Germany and the challenges it is facing. The state of society is viewed as "unbounded". In light of this result, what can political adult education contribute to saving the cohesion of a society? In answering this question, four current foci will be described: 1. The development of society, 2. The discussion about an understanding of education and politics, 3. The professional self-concept and the job image of those who work for institutions of political adult education, 4. The contemporary political issues and social changes and the answers that political education may be able to give.